Mental distress of physicians in the outpatient care throughout the COVID-19 pandemic: emotional and supportive human relations matter - Cross-sectional results of the VOICE-study - Sabine Mogwitz; Christian Albus; Petra Beschoner; Yesim Erim; Franziska Geiser; Lucia Jerg-Bretzke; Eva Morawa; Susann Steudte-Schmiedgen; Gloria-Beatrice Wintermann; Kerstin Weidner (BMC, 2023)
Abstract Background The aim of this cross-sectional study was to evaluate the course of self-reported mental distress and quality of life (QoL) of physicians, working in the outpatient care (POC). Outcomes were compared with a control group of physicians working in the inpatient care (PIC), throughout the Corona Virus Disease (COVID)-19 pandemic. The impact of risk and protective factors in terms of emotional and supportive human relations on mental distress and perceived QoL of POC were of primary interest. Methods Within the largest prospective, multi-center survey on mental health of health care workers (HCW), conducted during the first (T1) and second (T2) wave of the COVID-19 pandemic in Europe, we investigated the course of current burden (CB), depression (Patient Health Questionnaire-2), anxiety (Generalized Anxiety Disorder-2) and QoL, cross-sectionally, in n = 848 POC (T1: n = 536, T2: n = 312). The primary outcomes were compared with an age- and gender-matchted control group of n = 458 PIC (T1: n = 262, T2: n = 196). COVID-19-, work-related, social risk and protective factors were examined. Results At T1, POC showed no significant differences with respect to CB, depression, anxiety, and QoL, after Bonferroni correction. Whereas at T2, POC exhibited higher scores of CB (Cohen´s d/ Cd = .934, p < .001), depression (Cd = 1.648, p < 001), anxiety (Cd = 1.745, p < .001), work-family conflict (Cd = 4.170, p < .001) and lower QoL (Cd = .891, p = .002) compared with PIC. Nearly all assessed parameters of burden increased from T1 to T2 within the cohort of POC (e.g. depression: CD = 1.580, p < .001). Risk factors for mental distress of POC throughout the pandemic were: increased work-family conflict (CB: ß = .254, p < .001, 95% CI: .23, .28; PHQ-2: ß = .139, p = .011, 95% CI: .09, .19; GAD-2: ß = .207, p < .001, 95% CI: .16, .26), worrying about the patients´ security (CB: ß = .144, p = .007, 95% CI: .07, .22; PHQ-2: ß = .150, p = .006, 95% CI: .00, .30), fear of triage situations (GAD-2: ß = .132, p = .010, 95% CI: -.04, .31) and burden through restricted social contact in spare time (CB: ß = .146, p = .003, 95% CI: .07, .22; PHQ-2: ß = .187, p < .001, 95% CI: .03, .34; GAD-2: ß = .156, p = .003, 95% CI: -.01, .32). Protective factors for mental distress and QoL were the perceived protection by local authorities (CB: ß = -.302, p < .001, 95% CI: -.39, -.22; PHQ-2: ß = -.190, p < . 001, 95% CI: -.36, -.02; GAD-2: ß = -.211, p < .001, 95% CI: -.40, -.03; QoL: ß = .273, p < .001, 95% CI: .18, .36), trust in colleagues (PHQ-2: ß = -.181, p < .001, 95% CI: -.34, -.02; GAD-2: ß = -.199, p < .001, 95% CI: -.37, -.02; QoL: ß = .124, p = .017, 95% CI: .04, .21) and social support (PHQ-2: ß = -.180, p < .001, 95% CI: -.22, -.14; GAD-2: ß = -.127, p = .014, 95% CI: -.17, -.08; QoL: ß = .211, p < .001, 95% CI: .19, .23). Conclusions During the pandemic, the protective role of emotional and supportive human relations on the mental distress and quality of life of POC should be taken into account more thoroughly, both in practice and future research.